Building Sustainable Development Through Entrepreneurship Education in Nigeria - Oguntimehin, Abiodun (NIU Journal of Social Sciences, 2017)
In the developed nations, entrepreneurship education has been, and would continue to be a great economic stimulator. Entrepreneurship benefits cannot be overemphasized in any society that desires sustainable development, because it creates new technologies, production and services, encouraging improved productivity and rapid economic growth. Economic growth will invariably have positive influences on the health, thereby leading to sound body systems, increase in life span, improvement in social status and standard (condition) of living. Embracing and judicious application of entrepreneurship education principles will in no small measure propel Nigeria to the much desired enviable development level which she is currently yearning for. The focus of this paper is to discuss entrepreneurship education with particular attention to its concept, nature, objectives and development approaches.